Bach, the Goldberg variations - Williams, Peter, 1937 May 14-2016 (Cambridge music handbooks., 2001)
Many listeners and players are fascinated by Bach's Goldberg Variations. In this wideranging and searching study, Professor Williams, one of the leading Bach scholars of our time, helps them probe its depths and understand its uniqueness. He considers the work's historical origins, especially in relation to all Bach's Clavierübung volumes and late keyboard works, its musical agenda and its formal shape, and discusses significant performance issues. In the course of the book he poses a number of key questions. Why should such a work be written? Does the work have both a conceptual and a perceptual shape? What other music is likely to have influenced the Goldberg and to what extent is it trying to be encyclopedic? What is the canonic vocabulary? How have contemporaries or musicians from Beethoven to the present day seen this work and, above all, how has its mysterious beauty been created?--Publisher description.